A Study the Ecosystem Services (ES) of Industries and Urban Green Spaces (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This research was done to better understand the supply and demand for important ecosystem services, with a particular emphasis on the supplying, controlling, or cultural ecosystem services (ES) that the people of Nagpur City, a quickly developing urban center in Central India, utilize. In order to create a thematic map based on people's perceptions of demand and supply gaps in access to public urban green spaces (UGS), the study investigated participative tools. The participatory survey's goal was to learn about people's needs, the public UGS's accessibility and availability, & essential ES they were using. Urban planners & policy makers can use this information to gain a general understanding of Nagpur's green space availability & distribution. An inventive tool that has proven successful for documenting qualitative status, examining spatial distribution, and ranking UGS offerings is participatory mapping methodology. Incorporating participatory methods into geographic data can expand the advantages of UGS offerings. With the purpose of guaranteeing future urban sustainability through suitable & planned green infrastructure, these instruments aid in improved UGS governance.